Effectiveness of a Quartet-Based Educational Game in Improving Thalassemia Knowledge and Screening Awareness Among Senior High School Students - Annette d'Arqom; Mhd Zamal Nasution; Danti Nur Indiastuti; Kinesha Kostya; Nazwa Febry Savira; Junaidah Yusof (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Thalassemia is one of the most common genetic disorders in Indonesia, however, the knowledge and awareness are still low, especially in rural area. This study aimed to evaluate the effectiveness of a game-based educational tool to increasing knowledge and awareness about thalassemia among senior high school students in rural area. Methods: This quasi-experimental study explored the effectiveness of the Quartet card game in improving thalassemia knowledge and awareness among 93 high school students in rural East Java. An 11-item validated questionnaire was administered before and after the intervention. Their willingness to undergo the screening was measured in the end of the activity. Results: Prior to the intervention, the respondents had poor knowledge (2.3?±?2.8), which increased to a moderate level (7.4?±?2.9, p< 0.001) after the intervention. Even though there is an increase in knowledge and decrease in misconceptions, but some persisted, particularly regarding contagiousness and differentiation from leukemia. No associations were observed between knowledge improvement and demographic characteristics. Conclusion: The findings indicate that game-based education might enhance adolescent genetic literacy and may serve as a scalable strategy for health promotion. While effective in deliver fundamental concepts, additional strategies are needed to address persisted misconceptions and psychosocial aspects. Longer follow-up and more advanced or immersive serious games may help improve understanding and long-term knowledge retention.